FORMATION OF THE INFORMATION PORTRAIT OF THE AIRPORT - Oleshko Тamara (Proceedings of National Aviation University, 2014)
The approach for categorizing type classes of the airports by kinds of non-aviation activity with the help of the simplified information matrices using the methods of clustering analysis was studied in the article